Bioengineered fluorescent nanoprobe conjugates for tracking human bone cells: In vitro biocompatibility analysis - Salgado, CL (2021)
Herein, we validated novel functionalized hybrid semiconductor bioconjugates made of fluorescent quantum dots (QD) with the surface capped by chitosan (polysaccharide) and chemically modified with O-phospho-L-serine (OPS) that are biocompatible with different human cell sources. The conjugation with a directing signaling molecule (OPS) allows preferential accumulation in human bone mesenchymal stromal cells (HBMSC). The chitosan (Chi) shell with the fluorescent CdS core was characterized by spectroscopical (UV spectrophotometry and photoluminescence), by morphological techniques (Transmission Electron Microscopy (TEM)) and showed small size (ø 2.3 nm) and a stable photoluminescence emission band. The in vitro biocompatibility results were not dependent on the polysaccharide chain length (Chi with higher and lower molecular weight) but were remarkably affected by the surface modification (Chi or Chi-OPS). In addition, the efficiency of nanoparticles uptake by the cells was dependent on cells nature (human primary cells or cell lines) and tissue source (bone or skin) in the presence or absence of the OPS modification. The complex cellular uptake pathways involved in the cell labeling with the nanoparticles do not interfere on the normal cellular biology (adhesion and proliferation), osteogenic differentiation, and gene expression. The bone cells particles uptake evaluation showed a possible pathway by Caveolin-1 that regulates cell transduction in the membrane’s Caveolae. Caveolae mediates non-specific endocytosis, and it is upregulated in HBMSC. The OPS-modified nanoparticles promoted an intense intracellular trafficking by the HBMSCs that showed late-osteoblast phenotype with an increase of extracellular matrix (ECM) mineralization (Alizarin red and Von Kossa staining for calcium phosphate crystals). In this work, the OPS modified bioconjugated QD proved to be a reliable and stable fluorescent bioprobe for cell imaging and targeting research that could also help in clarifying some cellular mechanisms of particles intracellular traffic through the cytoplasmic membrane and osteogenic differentiation induction. The in vitro HBMSC’s biocompatibility responses indicated that the OPS-modified chitosan QDs have a prospective future in laboratory and pre-clinical applications such as bioimaging analysis and for ex-vivo cellular evaluation of biomedical implants.